Plankton Biodiversity in The Floating Net Cage - Permana, I Gede Wahyu; Setiabudi, Gede Iwan; Sitepu, Gressty Sari Br (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
Lake Batur has the potential to be a fishery resource that has not been explored and even very little attention from the community and the government so that this resource can be developed optimally. The current condition of lake Batur waters tends to change either naturally or annually or changes due to community activities around the lake. This study aims to determine the feasibility of lake Batur waters as a fish farming business field for the freshwater floating net cage system. Water samples to be tested for water quality and plankton were obtained directly at Lake Batur. The results of plankton abundance at each station were received, at station I (2.070 ind/l), station II (1.477 ind/l), station III (6.975 ind/l), and station IV (2.617 ind/l), station V (2.902 ind/l).  The parameters observed are water quality parameters in the form of brightness, temperature, pH, DO, Nitrates, Nitrites, and plankton abundance in Lake Batur Kintamani, Bangli. The results of research on the quality parameters at each station showed different values. The brightness parameters at 5 stations have values in the range of 246-480 cm, temperatures 26-28.3 °C, pH 7.5-8.3, DO 7.1-8.3 mg/L, Nitrates 0.36-0.66 ppm, and Nitrites 0.02-0.04. brightness.